(untitled) (European Journal of Marketing and Economics, 2026)
The main objective of the research paper is to accomplish a comparative analysis of the energy dependence of the EU member states. This objective is de-composited in several sub-objectives: First, to make a short literature review and a summary of the main ideas concerning energy dependence; Second, to clarify the methodology used for analysis of the energy dependence of the EU. Third, to analyze the nominal energy dependency of the EU, as well as the Union energy dependency by energy types.Fourth, to analyze the energy intensity of the economy of the European Union countries. The research and analytical methods used for the development of the paper involve comparative analysis of the available data on energy security indicators, graphical and table presentation of statistical and empirical data and survey of available legal and analytical research on the topic. Entirely secondary data sources have been used in the research. The research results comprise: - the introduction of two new concepts as a result of the analysis – the nominal energy dependency and the real energy dependency; - the construction of an energy dependency classifying scheme for the European Union member states; - the construction of an classification grid of the energy dependence of the EU member states by energy type. The research results present the author contribution to the research field of energy dependency. They add value not only in analytical terms but also pave the road for formulating further ideas and evidence-based recommendations on policy measures.